2002
DOI: 10.1097/00000658-200204000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results With Multimodal Adjuvant Therapy and Liver Transplantation for the Treatment of Hepatocellular Carcinomas Larger Than 5 Centimeters

Abstract: ObjectiveTo determine the long-term results of liver transplantation for hepatocellular carcinoma (HCC) measuring 5 cm or larger treated in a multimodality adjuvant protocol. Summary Background DataTransplant has been established as a viable treatment of HCC measuring less than 5 cm, but the results for larger tumors have been disappointing. Several studies have shown promising preliminary results when combining transplant with preoperative transarterial chemoembolization and/or perioperative systemic chemothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
280
3
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 380 publications
(293 citation statements)
references
References 28 publications
9
280
3
1
Order By: Relevance
“…However, it is a serious problem that immunosuppressants increase the incidence of skin cancer and sarcoma and induce cancer progression causing incremental fatality of transplant recipients (1-3), because malignant tumors in transplant recipients are frequently more aggressive than similar malignancy in the general population (4). In the field of liver transplantation, it has been accepted that liver transplantation is an effective treatment for small, unresectable hepatocellular carcinoma (HCC) 3 in patients with cirrhosis (5) and it was recently reported that a significant proportion of patients with HCC measuring 5 cm or larger can achieve long-term survival after liver transplantation in the context of multimodal adjuvant therapy (6). Therefore, as the indications for liver transplantation have gradually included the advanced HCC, such liver transplant patients have been especially exposed to the greater risk of HCC recurrence in addition to the incidental risk of other types of malignancy, such as skin cancer (7).…”
Section: Il-12 Gene Therapy Is An Effective Therapeutic Strategy Formentioning
confidence: 99%
“…However, it is a serious problem that immunosuppressants increase the incidence of skin cancer and sarcoma and induce cancer progression causing incremental fatality of transplant recipients (1-3), because malignant tumors in transplant recipients are frequently more aggressive than similar malignancy in the general population (4). In the field of liver transplantation, it has been accepted that liver transplantation is an effective treatment for small, unresectable hepatocellular carcinoma (HCC) 3 in patients with cirrhosis (5) and it was recently reported that a significant proportion of patients with HCC measuring 5 cm or larger can achieve long-term survival after liver transplantation in the context of multimodal adjuvant therapy (6). Therefore, as the indications for liver transplantation have gradually included the advanced HCC, such liver transplant patients have been especially exposed to the greater risk of HCC recurrence in addition to the incidental risk of other types of malignancy, such as skin cancer (7).…”
Section: Il-12 Gene Therapy Is An Effective Therapeutic Strategy Formentioning
confidence: 99%
“…Even if a particular patient in this subgroup might benefit from liver transplantation, the overall 5-year survival rate of 50% for the entire subgroup is not acceptable in the current era of donor organ shortages. 34,35 Several groups have proposed extensions of the Milan criteria for liver transplantation, but most studies that are cited in support of these proposals have been retrospective and have been based on analyses of explanted livers (ie, information not available before surgery). 24,[35][36][37][38][39] Recently, Mazzaferro et al 25 made an interesting contribution to this controversy in their retrospective review of pathology after liver transplantation for HCC in 1556 patients; 1112 of these patients had tumors that did not fulfill the Milan criteria.…”
Section: What Is the Goal: A Benefit For Individual Patients Or Survimentioning
confidence: 99%
“…34,35 Several groups have proposed extensions of the Milan criteria for liver transplantation, but most studies that are cited in support of these proposals have been retrospective and have been based on analyses of explanted livers (ie, information not available before surgery). 24,[35][36][37][38][39] Recently, Mazzaferro et al 25 made an interesting contribution to this controversy in their retrospective review of pathology after liver transplantation for HCC in 1556 patients; 1112 of these patients had tumors that did not fulfill the Milan criteria. In a subgroup of 283 patients not meeting the Milan criteria whose tumors were within the up-to-7 criteria (ie, HCCs with a maximum score of 7, with the score being the sum of the size of the largest tumor and the total number of tumors) and were not characterized by microvascular invasion, the overall 5-year survival rate was 71.2%.…”
Section: What Is the Goal: A Benefit For Individual Patients Or Survimentioning
confidence: 99%
“…Even the best preoperative imaging techniques can underestimate tumor burden in as many as 20% and significant progression in tumor size and number between imaging and LT after waiting period is not uncommon [9,10]. Additionally 10% to 15% nodules suspected to harbor HCC on pre-transplant imaging are reported benign following microscopic scrutiny of resection specimens by histopathologists [11].…”
mentioning
confidence: 99%